Study of In?uence of Vaginal Ph on the e?cacy of Dinoprostone gel for Induction of Labor - J Sowmya; T Vijaya Krishna (Asian Journal of Medical Research, 2020)
Background: Inducing labor is a procedure intended to trigger artificial contractions of the uterus that generally involve progressive erasure and dilation of the cervix. This will hopefully lead to the birth of a baby through the vaginal route. To assess the efficacy of dinoprostone gel in cervical maturation and its effect on vaginal pH. Subjects and Methods: The participants were grouped by their vaginal pH into two groups. Group, I included patients with vaginal pH 4.5 and Group II included vaginal pH >4.5 and the differences between the groups with respect to maternal age, parity, gestational age. Those women with minimal change in Bishop Score, received up to 3 doses of dinoprostone gel intracervically, 6 hours apart. Women, who had no change in Bishop Score at the end of induction with 3 doses of dinoprostone, were further reassessed. Results: There was no statistically pertinent relationship between the two groups in regard to maternal age, gestational age, parity, and initial Bishop Score. The mean maternal age in Group I was 25.9 years and Group II was 26.9 years. The mean gestational age was 39.5 weeks in group I and 38.9 weeks in group II. The majority of subjects were primigravidas (70 percent in group I and 63 percent in group II). The mean Bishop score before labor induction was 3.6 0.9 in Group I and 4 1.0 in Group II. Out of 200 cases, 33 (23.3 percent) needed an improvement in Oxytocin, 33 (33.3 percent) in Group I and 4 (13.3 percent) in Group II. The vaginal delivery rate was 90% in Group I and 87% in Group II. The Caesarean section was marginally higher in Group II (10 percent) compared with Group I (13 percent). Conclusion: Parity has a major impact on the pre-induction of the Bishop Score and the pH itself has a vaginal influence. Knowing the pre-induction vaginal pH may also be a helpful method for determining the outcome of PGE2 induction.